Discover the answers you need at Westonci.ca, where experts provide clear and concise information on various topics. Join our platform to connect with experts ready to provide detailed answers to your questions in various areas. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
Let's solve the given equation step-by-step:
[tex]\[ \sqrt{7} \div 49^x = \frac{1}{7} \][/tex]
First, we need to express the terms involving roots and powers in a common base. We know:
[tex]\[ \sqrt{7} = 7^{1/2} \][/tex]
Also, we can express 49 as a power of 7:
[tex]\[ 49 = 7^2 \quad \text{so} \quad 49^x = (7^2)^x = 7^{2x} \][/tex]
Now, substituting these into the original equation, we get:
[tex]\[ 7^{1/2} \div 7^{2x} = \frac{1}{7} \][/tex]
Using properties of exponents, specifically [tex]\(a^m \div a^n = a^{m-n}\)[/tex], we can simplify the left-hand side:
[tex]\[ 7^{1/2 - 2x} = \frac{1}{7} \][/tex]
Next, we rewrite [tex]\(\frac{1}{7}\)[/tex] as a power of 7. Since [tex]\(\frac{1}{7} = 7^{-1}\)[/tex], we now have:
[tex]\[ 7^{1/2 - 2x} = 7^{-1} \][/tex]
Since the bases (7) are the same on both sides of the equation, we can set the exponents equal to each other:
[tex]\[ \frac{1}{2} - 2x = -1 \][/tex]
To isolate [tex]\(x\)[/tex], we solve the equation step-by-step:
1. Add 1 to both sides:
[tex]\[ \frac{1}{2} - 2x + 1 = -1 + 1 \][/tex]
[tex]\[ \frac{1}{2} + 1 - 2x = 0 \][/tex]
2. Combine the constants on the left side:
[tex]\[ \frac{1}{2} + \frac{2}{2} - 2x = 0 \][/tex]
[tex]\[ \frac{3}{2} - 2x = 0 \][/tex]
3. Add [tex]\(2x\)[/tex]:
[tex]\[ \frac{3}{2} = 2x \][/tex]
4. Divide both sides by 2 to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{3}{2} \div 2 = \frac{3}{4} \][/tex]
Thus, we find:
[tex]\[ x = \frac{3}{4} \][/tex]
The step-by-step solution demonstrates that the value of [tex]\(x\)[/tex] that satisfies the given equation [tex]\(\sqrt{7} \div 49^x = \frac{1}{7}\)[/tex] is:
[tex]\[ x = \frac{3}{4} \][/tex]
[tex]\[ \sqrt{7} \div 49^x = \frac{1}{7} \][/tex]
First, we need to express the terms involving roots and powers in a common base. We know:
[tex]\[ \sqrt{7} = 7^{1/2} \][/tex]
Also, we can express 49 as a power of 7:
[tex]\[ 49 = 7^2 \quad \text{so} \quad 49^x = (7^2)^x = 7^{2x} \][/tex]
Now, substituting these into the original equation, we get:
[tex]\[ 7^{1/2} \div 7^{2x} = \frac{1}{7} \][/tex]
Using properties of exponents, specifically [tex]\(a^m \div a^n = a^{m-n}\)[/tex], we can simplify the left-hand side:
[tex]\[ 7^{1/2 - 2x} = \frac{1}{7} \][/tex]
Next, we rewrite [tex]\(\frac{1}{7}\)[/tex] as a power of 7. Since [tex]\(\frac{1}{7} = 7^{-1}\)[/tex], we now have:
[tex]\[ 7^{1/2 - 2x} = 7^{-1} \][/tex]
Since the bases (7) are the same on both sides of the equation, we can set the exponents equal to each other:
[tex]\[ \frac{1}{2} - 2x = -1 \][/tex]
To isolate [tex]\(x\)[/tex], we solve the equation step-by-step:
1. Add 1 to both sides:
[tex]\[ \frac{1}{2} - 2x + 1 = -1 + 1 \][/tex]
[tex]\[ \frac{1}{2} + 1 - 2x = 0 \][/tex]
2. Combine the constants on the left side:
[tex]\[ \frac{1}{2} + \frac{2}{2} - 2x = 0 \][/tex]
[tex]\[ \frac{3}{2} - 2x = 0 \][/tex]
3. Add [tex]\(2x\)[/tex]:
[tex]\[ \frac{3}{2} = 2x \][/tex]
4. Divide both sides by 2 to solve for [tex]\(x\)[/tex]:
[tex]\[ x = \frac{3}{2} \div 2 = \frac{3}{4} \][/tex]
Thus, we find:
[tex]\[ x = \frac{3}{4} \][/tex]
The step-by-step solution demonstrates that the value of [tex]\(x\)[/tex] that satisfies the given equation [tex]\(\sqrt{7} \div 49^x = \frac{1}{7}\)[/tex] is:
[tex]\[ x = \frac{3}{4} \][/tex]
Thanks for using our platform. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Get the answers you need at Westonci.ca. Stay informed with our latest expert advice.